Some integral operators of Buschman-Erdélyi type - Virchenco, N. (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
New integral operators involving the generalized Legendre function Pr-n(z) are introduced. Sorne integrals are evaluated.